Teacher Professional Development In The Context Of Independent Learning - Riska Nadia (Nusantara Education, 2023)
To improve the quality of education and anticipate the demands of competence and learning in the era of the Industrial Revolution 4.0, The Ministry of Education and Culture of the Republic of Indonesia launched a policy known as “Merdeka Belajar"(Freedom for Learning"). The essence of Merdeka Belajar is to explore the greatest potential of school teachers and students to innovate and improve the quality of learning independently. Freedom for learning requires teacher “Merdeka Mengajar” (Freedom to Teach), where teachers freely apply their professional autonomy in improving the quality of learning and student learning outcomes. Merdeka Mengajar can only be done by professional teachers and can adapt and face the challenges of science and technological advances throughout their careers. This suggests the need for continuous professional development of teachers so that teachers become as lifelong learner. Teacher professional development must address the problems and needs of teachers in improving student learning processes and outcomes. Therefore, the teacher professional development model that is considered the most appropriate is the school-based teacher professional development. School-based teacher professional development can make teachers as a professional learning community.